The Effectiveness Of Village Microfinance Financing Program By Baznas In Encouraging The Development Of Micro-Entreprises - Jasri, Jasri; Wahdah, Andi Syarifah; Malik, Abdul (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
This research aims to identify how the implementation of the village microfinance program by Baznas affects the development of micro-enterprises owned by the beneficiaries in BAZNAS Maros Regency. The research methodology employed in this study involves a qualitative approach with a descriptive nature. Data collection methods include observations, face-to-face interviews, and documentation. The research findings reveal that the execution of the Village Microfinance program by the National Zakat Agency in Maros Regency significantly contributes to micro-entrepreneurs in enhancing their businesses, especially those facing difficulties in accessing capital. The program also assists micro-entrepreneurs in mitigating the decreased income impacts caused by the COVID-19 pandemic. In addition to financial support, beneficiaries entering the micro-business sector also receive market access support from the BAZNAS Village Microfinance program, aiding them in promoting their commercial products more effectively.